Wastewater Treatment Engineering 2015
DOI: 10.5772/60924
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Biological Treatment of Sanitary Landfill Leachate

Abstract: Landfilling, one of the prevailing worldwide waste management strategies, is presented together with its benefits and environmental risks. "side from biogas, another non-avoidable product of landfilling is landfill leachate, which usually contains a variety of potentially hazardous inorganic and organic compounds. It can be treated by different physico-chemical and biological methods and their combinations. The composition and characteristics of landfill leachate are presented from the aspect of biotreatabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 77 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Conventional treatment methods, although effective, are environmentally harmful to landfill leachate treatment and are also technologically expensive (Dursun 2006;Fan et al 2008;Hermosilla et al 2009). Although many chemical and physical methods have been used to treat leachate (Akgul et al 2013;Gotvajn and Pavko 2015), many authors have confirmed, for example, the ability of carbon as an adsorbent to remove various inorganic and organic pollutants (Al-Saadi et al 2013;Saleh and Gupta 2014). The use of adsorbents is a widely accepted approach for removing pollutants from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment methods, although effective, are environmentally harmful to landfill leachate treatment and are also technologically expensive (Dursun 2006;Fan et al 2008;Hermosilla et al 2009). Although many chemical and physical methods have been used to treat leachate (Akgul et al 2013;Gotvajn and Pavko 2015), many authors have confirmed, for example, the ability of carbon as an adsorbent to remove various inorganic and organic pollutants (Al-Saadi et al 2013;Saleh and Gupta 2014). The use of adsorbents is a widely accepted approach for removing pollutants from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The probable presence of non-biodegradable emerging pollutants is also of concern. The outcome is thus unsatisfactory and requires the inclusion of an additional treatment step to meet the discharging standards [13][14][15][16]. Recently, AOPs are considered to be among the most efficient methods in disinfecting and purifying ground water and natural water, as well as being used in wastewater treatment [17,18].…”
Section: Introductionmentioning
confidence: 99%